191k views
5 votes
(sinx + cosx)(1 − sinx cosx) ≡ sin3x + cos3x

User Ian Flynn
by
5.1k points

1 Answer

4 votes

Explanation:

We will use the LHS to find the RHS.

Step 1: Expand the LHS by multiplying through the brackets and simplify

(sinx + cosx)(1 − sinx cosx) ≡ sinx + cosx - (sinx + cosx (sinx cosx))

≡ sinx + cosx - sin²x cosx - sinx cos²x

Step 2: Use the identity sin²x + cos²x = 1, to rewrite the equation

≡ sinx + cosx - cosx (1 - cos²x) - sinx (1 - sin²x)

Step 3: Simplify the equation by adding like terms

≡ sinx + cosx - cosx + cos³x - sinx + sin³x

≡ sin³x + cos³x [QED]

Reminder:

  • 1 - cos²x = sin²x
  • 1 - sin²x = cos²x
  • (cosx)(cosx) = cos²x

User Philonous
by
4.5k points